(untitled) (Italian Review of Legal History, 2017)
The essay means to reconstruct the dynamics, and the main themes below, of a technically complex and politically very delicate phase of the 1890’s judicial reform taken up by the statesman and jurist Giuseppe Zanardelli: the section dedicated to the “Modification of the judicial district and improvement of the judiciary salaries” (law 30 March 1890 n. 6702). The reconstruction is based on archive documentation, largely unpublished: not only official documents, but also personal notes, memories, letters, note books, which recorded aspirations, moods, utopic feelings, compromises nourished by historical characters who participated in the reformation movement. Their analysis, besides allowing an adequate technical comprehension of the judicature’s genesis in the unified Italy and of the able and pragmatic role played by Zanardelli, could also be the opportunity to launch the gaze through a cut-out of the building that was growing. The unitary state for which the judiciary was inevitably not only one of its powers, but often also the “first line” contact between citizens and State.